Interrelationships Between 1,25 Vitamin D, and iPTH, in Progressive CKD: A Cross-Sectional Study - Haider Hussain, Rafal; S. Haddad, Nazar; Jasim Alsultani, Ali (Hammurabi Journal of Medical Sciences, 2024)
Background: Chronic kidney disease (CKD) has become a growing global health concern affecting nearly 700 million individuals and accounting for 4.6% of all annual deaths worldwide. The condition is defined with decreased renal function quantified by glomerular filtration rate (GFR) and evidence of kidney injury evidenced by proteinuria determined by the urine albumin-to-creatinine ratio (ACR). Objectives: this study was to investigate the association of 1,25(OH)2 D with iPTH in patients with progressive CKD. Materials and Methods: This study was cross-sectional and conducted at Al-Imam Al-Sadiq Hospital, Babil, Iraq. This study enrolled 164 patients (84 men and 80 women) with CKD stages 2-5. Patients were grouped by CKD stage: 20 stage 2 patients and 36 stage 3a, 3b, 4, and 5 patients. Inclusion criteria were derived from established CKD markers, including albuminuria and decreased GFR. Exclusion criteria included diagnosis of primary hyperparathyroidism, prior parathyroidectomy, pregnancy and lactation. Serum levels of urea, creatinine, 25 (OH) D, 1,25 (OH)2 D and intact Parathyroid Hormone (iPTH) were measured on blood sample. With regard to loacl factors, samples of urine were collected to evaluate microalbuminuria. Vitamin D and PTH were measured via ELISA, while the other parameters were determined by standard biochemical methods. Results: The study revealed a strong positive correlation between estimated Glomerular Filtration Rate (eGFR) and 1,25(OH)2 D levels, with a correlation coefficient of 0.545 (p < 0.01), a strong negative correlation between eGFR and iPTH levels (correlation coefficient of -0.587, p < 0.01), and a moderate negative correlation between 1,25 (OH)D and iPTH levels (correlation coefficient of -0.422, p < 0.01). Conclusion: This study showed a strong relationship between rising iPTH levels and a decline in 1,25 OH D with decreased eGFR (deteriorating CKD).